INFLUENCE OF INFORMATION QUALITY AND SYSTEM QUALITY AND QUALITY OF DIGITAL PAYMENTS ON CONSUMER SATISFACTION AND REPURCHASING INTENTION ON GOJEK USERS IN THE CITY OF SAMARINDA - Achmad Fachri; Syarifah Hudayah; Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine and analyze the direct and indirect effect of Mobile Service Quality (Information Quality, System Quality, and Digital Payment Quality) on Consumer Satisfaction and Repurchase Intention of Gojek Users in Samarinda City.The study was conducted by purposive sampling to Gojek users in Samarinda City as many as 91 (ninety one) people using Google Form. The data were then analyzed using the Partial Least Square method. The results showed that: 1) The quality of information has a positive and insignificant effect on consumer satisfaction; 2) Information quality has no significant negative effect on users' repurchase intentions; 3) The quality of the system has a significant positive effect on customer satisfaction; 4) System quality has no significant positive effect on repurchase intention; 5) Payment quality has no significant positive effect on customer satisfaction; 6) The quality of digital payments has a significant positive effect on repurchase intentions; 7) Consumer satisfaction has no significant positive effect on repurchase intention; 8) Information quality has no significant positive effect on repurchase intention through consumer satisfaction; 9) System quality has no significant positive effect on repurchase intention through consumer satisfaction; 10) The quality of digital payments has an insignificant positive effect on repurchase intentions through consumer satisfaction of Gojek users in Samarinda City. Keywords: Information Quality; System Quality; Digital Payment Quality, Consumer Satisfaction; Repurchase Intention, Mobile Service Quality